Dexamethasone reverses the effects of high glucose on human retinal endothelial cell permeability and proliferation in vitro. (October 2016) - Stewart, E.A.; Saker, S.; Amoaku, W.M.
Abstract: Diabetic macular oedema (DMO), a leading cause of preventable visual loss in the working population, is caused by an increase in microvascular endothelial cell permeability, and its prevalence is on the increase in parallel with the rising worldwide prevalence of diabetes. It is known that retinal vascular leakage in DMO is contributed to by VEGF upregulation as well as non-VEGF dependent inflammatory pathways, and the potential use of anti-inflammatory agents such as the glucocorticoids, including dexamethasone are being extensively studied. However, the mechanisms of action of dexamethasone in DMO reduction are not fully understood. Using human primary retinal endothelial cells (REC) the in vitro effect of dexamethasone in modulating the proliferation, permeability and gene expression of key tight and adheren junction components, and the expression of angiopoietins (Ang) 1 and 2 in high (25 mM) glucose conditions were investigated. High glucose decreased REC proliferation, an effect that was reversed by dexamethasone. High glucose conditions significantly increased REC permeability and decreased claudin-5, occludin and JAM-A gene expression; dexamethasone was effective in partially reversing these changes, restoring EC permeability to the normal or near normal state. High glucose levels resulted in reduction of Ang1 secretion, although Ang2 levels were consistently high. DEX increased Ang1 and decreased Ang2, indicating that the balance of Ang1/Ang2 may be important in determining functional changes in REC under high glucose conditions. Highlights: Diabetic retinopathy causes most blindness in the working population. Visual loss is caused by fluid (oedema) due to increased endothelial permeability. Hyperglycaemia increases human retinal endothelial permeability in vitro . Increased permeability was reversed by dexamethasone. Dexamethasone molecular changes induced by high glucose.